Fuzzy sequential model for strategic planning of small and medium scale industries - Imam Santoso; Puspa Ayu Indah Prameswari; Aulia Bayu Yushila; Muhammad Arwani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The use of strategic planning can be an alternative solution to improve industrial performance. In small and medium scale industries especially in apple chips industries, strategic planning helps to know the current industry situation and the steps that must be taken to overcome the existing problems. This study aimed to develop an improvement strategies using Fuzzy Sequential Modeling (FSM) model. FSM model was consisted a SWOT analysis, Root Cause Analysis (RCA), Bolden’s Taxonomy and fuzzy AHP. Based on SWOT analysis, the external factors of threats was the similar business competition and low purchasing power. RCA described the issues that needed to be fixed using Bolden’s Taxonomy as the reference for determining the action plans and produce four OIA (Open Improvement Area) there are old technology machines and equipment, difficulty of enterprise development, ineffective marketing media and low market share. The strategic planning was determined using Fuzzy AHP based on OIA and ABC enterprise needs to improve the low market share and ineffective marketing strategy.